PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA DI TEMPAT OLAH SAMPAH SETEMPAT WERDI GUNA DESA GUNAKSA KABUPATEN KLUNGKUNG - I Putu Dedi Wiriastika; I Nyoman Setiawan; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2022)
The use of renewable energy is a solution in the application of clean andenvironmentally friendly energy, one of which is the use of solar power with the PLTS system. Inthis study, the PLTS system planned at TOSS Werdi Guna is a PLTS-On Grid system without abattery with a ground mounted installation, the aim is to reduce the cost of electricity bills. PLTSplanning at TOSS Werdi Guna has a capacity of 32.6kWp with a number of 86 modules anduses 1 inverter unit with a capacity of 33kW. The energy production produced by PLTS for ayear is 52,955kWh. The total investment cost required is IDR 580,469,095 with a paybackperiod of 7 years and 4 months.